PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI PT KERETA API INDONESIA DAOP 8 SURABAYA - ARIF MASUM, MOH (Jurnal Ilmu Manajemen (JIM), 2017)
This study aims to determine and analyze the influence of leadership style and organizational culture in PT Kereta Api Daop 8 Surabaya on employee performance. This research uses descriptive analysis method and multiple linear regression analysis. Data processing is done by using PLS 2.0 for windows. The sample for this research is 98 employees at PT Kereta Api Indonesia Daop 8 Surabaya. The results showed that leadership style has a significant effect on employee performance, this is evidenced by the value of t arithmetic of 5,3572 is greater than the value of t table of 1,965. And organizational culture shows that organizational culture has a significant influence on employee performance is evidenced by the value of t arithmetic of 5,0224 greater than the value of t table of 1,965. key words: employee performance, organizational culture, leadership style